How often an isolated cardiac disproportion predicts a coarctation of the aorta? Single center experience and systematic review of the literature. (19th May 2018) - Ghi, Tullio; Dall'Asta, Andrea; Cavalli, Claudio; Galli, Letizia; Weiss, Adi; Pedrazzi, Giuseppe; Kaihura, Christine Tita; Volpe, Nicola; Agnetti, Aldo; Frusca, Tiziana
Abstract: Background: Cardiac disproportion is considered as an indirect sign of coarctation of the aorta (CoA). In this review, we have reassessed the positive predictive value (PPV) of such finding for a postnatal confirmation of CoA. Data sources: All cases of isolated cardiac disproportion diagnosed in the four-chamber and/or three-vessel/three-vessel and trachea views (right/left sections >1.5) were included. Postnatal cardiac findings were recorded. Additionally, a systematic literature search (PubMed, EMBASE, Cochrane library, and the reference lists of identified articles) regarding the association between antenatally detected cardiac disproportion and postnatal confirmation of CoA was performed. Data from our center were pooled with those derived from the literature. Results: Ten fetuses with isolated cardiac disproportion were selected from our center and 259 from the literature review. CoA was postnatally confirmed in 101/269 (PPV 38%). PPV of antenatal cardiac findings was significantly higher in earlier gestation (23/27, 85% <26 +0 weeks versus 11/39, 28%≥26 +0 weeks, p < .001). No significant difference was noticed comparing ventricular disproportion with combined ventricular and great vessels disproportion (86/230 versus 15/39, p .89). Discussion: Isolated cardiac disproportion has an overall chance of one in three of heralding a CoA in the neonate. The specificity of these findings is significantly higher in the second trimester.